The impact of special economic zones on electricity intensity of firms - Ronald B. Davies; Arman Mazhikeyev; T. Huw Edwards (University College Dublin, UCD School of Economics, 2016)
In light of concerns over the environmental impact of Special Economic Zones located in developing countries, where environmental regulation is weak, we analyse the electricity intensity of firms in SEZs. We use firm level data from Africa and Asia, and we find that SEZ firms have higher electricity intensity as opposed to non-SEZ firms. If they also face higher fiscal, financial or environmental regulations, the electricity intensity of firms in SEZs increases by a greater rate as opposed to non-SEZ firms. As such, establishing SEZs may have significant environmental implications.
Keywords: F14; J16; 330; Energy Intensity; Special Economic Zones